Incidence of low anterior resection syndrome and its association with the quality of life in patients with lower rectal tumors - Homma, Yuko; Mimura, Toshiki; Koinuma, Koji; Horie, Hisanaga; Sata, Naohiro (Surgery today (Tokyo, Japan), 2024)
Purpose Low anterior resection syndrome (LARS) causes devastating symptoms and impairs the quality of life (QOL). This study investigated the incidence and risk factors of LARS and their association with the QOL in patients with lower rectal tumors. Methods Patients who underwent anus-preserving surgery for lower rectal tumors between 2014 and 2019 and who had anal defecation between 2020 and 2021 were surveyed. The LARS score measured severity, and the QOL was evaluated using the Japanese version of the Fecal Incontinence Quality-of-Life Scale (JFIQL). The primary endpoint was the incidence of Major LARS, and the secondary endpoints were risk factors and association with the JFIQL. Results Of 107 eligible patients, 82 (76.6%) completed the LARS survey. The incidence of Major LARS was 48%. Independent risk factors included neoadjuvant chemoradiotherapy (CRT) and a short interval (< 24 months after surgery; odds ratio, 4.6; 95% confidence interval: 1.1–19, both). The LARS score was moderately correlated with the JFIQL generic score (correlation coefficient: − 0.54). The JFIQL scores were significantly worse in the Minor and Major LARS groups than in the No LARS group. Conclusions Major LARS was found in 48% of lower rectal tumors, and independent risk factors include neoadjuvant CRT and a short interval. The QOL was significantly impaired in patients with both Minor and Major LARS.